Association between serum Klotho concentration and all-cause and cardiovascular mortality among American individuals with hypertension - Yan, Yuqin; Chen, Jun (Frontiers in Cardiovascular Medicine, 2022)
Background and Aims: Evidence indicates that serum Klotho concentration is associated with mortality in patients with chronic kidney disease. However, evidence on this association among people with hypertension is scarce. Therefore, we aimed to examine the association between serum Klotho concentration and all-cause and cardiovascular mortality in American patients with hypertension. Methods and Results: We included 6778 participants with hypertension from the National Health and Nutrition Examination Survey 2007–2014. A Cox proportional hazard model was used to compute the hazard ratios (HRs) and 95% confidence intervals (CIs). The correlation between serum Klotho concentration and mortality was determined using restricted cubic spline and piecewise linear regression analyses. During 36714 person-years of follow-up, 575 deaths were documented. Lower serum Klotho concentration was associated with increased all-cause mortality, but not cardiovascular mortality after multivariate adjustment. According to spline analysis, the correlation between serum Klotho concentration and all-cause mortality was nonlinear (P<0.001), and the threshold value was 574 pg/mL. The HR below the threshold point was 0.79 (95% CI: 0.67–0.93); no significant difference was found above the threshold point. Conclusions: Higher serum Klotho concentration was associated with lower all-cause mortality, but not cardiovascular mortality in patients with hypertension with or without chronic renal impairment.